Bosniaks on the island of Krk and in the town of Buzet - Škiljan, Filip (Historical Thought, 2025)
In this paper the author explores two communities of Bosniaks in the town of Buzet and on the island of Krk. The research of settlements of labor migrants of Muslims from Bosnia and Herzegovina in the area of Krk island was undertaken in August 2013. On that occasion, interviews were conducted with representatives of Bosniaks/Muslims in the Krk area that are situated in Omišalj, Njivice, Malinska, Sveti Vid, Gostinjac and Polje. Researching Bosniaks in Buzet was undertaken in September 2013 and on this occasion Bosniaks/Muslims from the town of Buzet were interviewed. The paper includes statements from the interviews, the documents from the Central Bureau of Statistics, the documentation of the Bosniak national community in Croatia and available literature.